CMP604: Infromation technology for communication management / Faculty of Communication and Media Studies - UiTM, Faculty of Communication and Media Studies (2022)
Data, digital technologies and devices drive organisation strategy and operations. This new era of information technology has created by the convergence of social, mobile, big data, analytics, cloud, sensor, software-as-a service and data visualization technologies. These technologies enable real-time insights, organisation decisions and actions. This course examines the role of new information technology in contemporary society and the evolution of media technologies and innovation in organisation as moving towards the era of Fourth Industrial Revolution. Students will utilize and practice with various new media tools and platforms for personal, professional and innovation contexts. This course will also explore best practices in the use of social networks and social media in strategic communication activities. Students will be exposed to the strategic uses of new media and real world case studies illustrating how organisation’s strategies increase productivity, improve efficiency , enhance communication and collaboration, and gain a competitive edge through the use of ITs. Topics covered will include data governance strategy, cybersecurity, cloud computing, social media strategies and metrics and how to integrate new media to the advantage of the organisation.